Extraction and characterization of arabinoxylans obtained from nixtamalized brewers' spent grains - Martínez-Encinas, Efrén G (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2023)
The processes to obtain value-added products from brewers' spent grain, a contaminant industrial waste, require alkaline non-ecofriendly pre-treatments. The arabinoxylans from brewers' spent grain were extracted by nixtamalization evaluating the extraction procedure, antioxidant capacity and molecular characteristics. The best arabinoxylans yields were those extracted with CaO at 100 °C and 25 °C (6.43% and 3.37%, respectively). The antioxidant capacity by 2,2-diphenyl-1-picrylhydrazyl assay of the arabinoxylans after thermal treatment and additional arabinoxylans after thermal treatment proteolysis were 434 and 118 mg TE/g, while by 2,20'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) diammonium salt assay the value was similar (380 μmol TE/g). The intrinsic viscosities and viscosimetric molecular weights were 69 mL/g and 13 kDa for arabinoxylans after thermal treatment, and 15 mL/g and 1.6 kDa for arabinoxylans after thermal treatment proteolysis, respectively. The protein and lignin contents were 3.1% and 6.4% for arabinoxylans after thermal treatment and, 0.9% and 4.6% for arabinoxylans after thermal treatment proteolysis, while their arabinose: xylose ratios were 0.39 and 0.36, with ferulic acid contents of 0.63 and 0.14 mg/g, respectively. Both products of arabinoxylans were molecularly identical by Fourier transform infra-red. Although the purity of the extracted arabinoxylans was improved with proteolysis, their intrinsic viscosity and viscosimetric molecular weight were affected. The extraction of arabinoxylans from brewers' spent grain by CaO nixtamalization alone or after additional proteolysis was successful to obtain purity and good antioxidant capacity